Pengaruh Publikasi Publikasi Laporan Arus Kas terhadap Volume Perdagangan Saham Perusahaan di Bursa Efek Jakarta - Ambar Woro Hastuti; Bambang Sudibyo (The Indonesian Journal of Accounting Research, 2013)
The efficient market hypotheses state that security prices instaneously reflect all relevant available information. In other words, the investment decisions made by the investors are a reaction to the information received by them. The financial statements published consist of specific information about the firm, and in the Financial Accounting Standards (Standar Akuntansi Keuangan) No. 2 the Cash-Flow Statements as part of financial statements must be published since January 1, 1995.The objective of this study, is to investigate whether Cash-Flow Statements influence investors decisions. This is expected to be reflected in the change of the average relative trading volume activity (TVA) around the dates of financial statements published two years prior to two years after Cash Flow Statements are publications.Analysis of 37 security samples indicate that: (1) For financial statements of December, 31 1991 and 1992, TVA did not significantly relate to the financial statement published, while for the financial statements of December, 31 1993 and 1994 TVA related significantly to the financial statements published. This results provide empirical evidence that investors react to the financial statements as of Desember , 31 1993 and 1994. (2) There is a significant difference between TVA two years prior with two years after Cash Flows Statements publication. The result indicates that TVA prior Cash Flow Statements publication ( TVA 1991 = O,1355,   1992 = 0,0745) and after Cash Flows Statements publication  TVA 1993 = 0,0927, TVA 1994 = 0,0711). In fact these significantly difference caused of TVA three days around the financial statements Desember, 31 1991 publication date relatively higher to 1992, 1993, and 1994. Is probably caused of bullish condition in Indonesian stock market in 1989 up to 1990, where many investors bought the stocks without really considering the information contains in the financial statements. This case were also supported by the result of first hyphotheses in this research, and the findings of Papilaya (1989) and Hendrayati (1992) indicate that the investors did not use financial information in investment decision making.Keywords:       Financial Statements, Cash-Flows Statements, Trading Volume Activity